Formate hydrogen production catalyst and preparation and application thereof

By using hydrothermal treatment in the formate hydrolysis hydrogen production catalyst to prepare spindle-shaped Cr-based materials and load Pd and Ni nanoparticles, the problems of low catalyst activity and high CO2 release are solved, and efficient hydrogen production and hydrogen storage cycles are achieved. Reduced costs.

CN119237016APending Publication Date: 2025-01-03CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310770313.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing formate hydrolysis hydrogen production catalyst has low activity, easy deactivation of catalyst materials, high by-product CO2, and high cost of relying on precious metals, which cannot meet the requirements of hydrogen-energy vehicles or large-scale storage and long-distance transportation.

Method used

Spindle-shaped Cr-based materials are prepared by hydrothermal treatment of the Cr source, the aqueous solution of formula 1 and HF, and Pd and Ni nanoparticles are deposited thereon, controlling the proportion, concentration, hydrothermal temperature and molar of Pd/Ni of HF. to improve the reactivity and stability of the catalyst.

Benefits of technology

It realizes efficient production of hydrogen under low temperature conditions, with hydrogen yield up to 80mol·H2/h/kg·catalyst, hydrogen concentration up to 80vol%, and formate is regenerated through hydrogenation reaction, realizing hydrogen storage and discharge cycle, reducing The release of CO2 improves the selectivity and stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237016A_ABST
    Figure CN119237016A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalytic hydrogen production, in particular to a preparation method of a formate hydrogen production catalyst, an aqueous solution containing a Cr source, a compound of formula 1 and HF is subjected to hydro-thermal treatment, and in the aqueous solution, the molar ratio of the Cr element to the compound # imgabs0 # HF of formula 1 to water is 1: 1-2: 1-2.5: 270-290; the hydrothermal temperature is 190-230 DEG C, and the hydrothermal time is 7-13 hours; carrying out solid-liquid separation after hydrothermal treatment, and washing to obtain a spindle type Cr-based material; nano active particles are deposited on a spindle type Cr-based material to prepare the formate hydrogen production catalyst, the nano active particles are Pd and Ni simple substances and alloys thereof, and the molar ratio of Pd to Ni is 1: (1.5-3); the content of the nano active particles is greater than or equal to 1wt%. The invention also comprises the catalyst prepared by the preparation method and application of the catalyst in formate hydrogen production. The process disclosed by the invention is beneficial to catalyzing formate to produce hydrogen and improving the hydrogen production performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen production, and in particular to the technical field of formate hydrogen production catalysts. Background Art

[0002] The continuous consumption of fossil fuels has led to increasing greenhouse gas emissions, and the continuous development of social economy has put forward new requirements for energy demand and the proportion of clean energy. Looking at the history of human fuel evolution, from coal to oil and then to the natural gas currently widely used in Europe, this evolutionary trajectory is along the direction of increasing hydrogen content, and the use of pure hydrogen will be the end point of this evolution. As the cleanest fuel, the calorific value of hydrogen is three times that of oil, but unfortunately, hydrogen is more difficult to store than oil, which has spawned problems such as high hydrogen cost and market supply shortage, which has become the biggest obstacle to the application of hydrogen in specific scenarios such as hydrogen-powered vehicles. Not only that, immature hydrogen storage technology has also spawned a series of safety issues. At present, the imperfection of high-capacity hydrogen storage technology has become one of the key factors restricting the use of hydrogen energy.

[0003] At present, the mainstream hydrogen storage methods include high-pressure gaseous hydrogen storage, low-temperature liquid hydrogen storage, solid material hydrogen storage and chemical hydrogen storage. High-pressure gaseous hydrogen storage technology is relatively mature and widely used, but it has problems such as low volume hydrogen storage density and potential safety hazards in transportation; although low-temperature liquid hydrogen storage has a higher volume hydrogen storage density, it is expensive and easy to volatilize, which is not conducive to long-term storage; chemical hydrogen storage technology has advantages in safety, hydrogen storage density and long-term storage, but the existing chemical hydrogen storage technology cannot meet the requirements of hydrogen-powered vehicles or large-scale storage and long-distance transportation of hydrogen, and further theoretical research on chemical hydrogen storage is necessary. Among the many chemical hydrogen storage materials currently under study, formate has become one of the most promising hydrogen storage candidate materials due to its mild hydrogen desorption conditions, cheap and easy-to-obtain raw materials, few by-products of hydrogen desorption reactions and easy handling.

[0004] Formate is usually solid at room temperature, so it is very convenient for long-distance transportation and long-term storage. More importantly, formate is usually very soluble in water. Its aqueous solution can be decomposed into CO2 and H2 under the action of a suitable catalyst at room temperature and pressure, and theoretically can produce a small amount of CO2, which makes formate more in line with the requirements of the "3060" dual-carbon target as a hydrogen storage material. On the other hand, the bicarbonate produced by the decomposition of formate can be used as a CO2 carrier, and formate can be regenerated by hydrogenation reaction by obtaining hydrogen resources from the outside, thereby completing the reversible cycle of hydrogen storage and release based on formate-bicarbonate. However, although formate has many advantages in hydrogen production, in the previous reaction system of formic acid catalytic decomposition to produce hydrogen, formate was only used as an auxiliary reagent for adjusting the pH of the solution. At present, there are few systematic studies specifically on the catalytic dehydrogenation of pure formate solution, and the similarities and differences between its dehydrogenation mechanism and the dehydrogenation mechanism of formic acid are still unclear. How to improve the hydrogen yield in the hydrolysis process of formate and reduce the release of CO2 in the hydrolysis process of formate to achieve zero emission of carbon oxides is an urgent problem to be solved.

[0005] At present, there are relatively few studies on heterogeneous catalysts for hydrogen production from formate solutions. Existing studies have shown that palladium-based catalysts and ruthenium-based catalysts exhibit good activity in the dehydrogenation process of formate solutions. Although domestic and foreign scholars have achieved certain results in the study of the reversible hydrogen storage and release reaction of formate-bicarbonate, the catalysts for this reaction still have problems such as low catalytic activity, low hydrogen production, easy deactivation of catalyst materials, and high by-product CO2. Summary of the invention

[0006] In view of the problems of low activity of existing formate hydrolysis hydrogen production catalysts, easy deactivation of catalyst materials, high by-product CO2, and high cost caused by catalyst dependence on precious metals, the present invention proposes a method for preparing a formate hydrogen production catalyst, aiming to prepare a catalyst with excellent formate hydrogen production activity and stability.

[0007] The second object of the present invention is to provide a catalyst prepared by the preparation method and its application in hydrogen production from formate.

[0008] The third object of the present invention is to provide a formate-mediated hydrogen production and storage method.

[0009] Different from formic acid hydrogen production, formate hydrogen production has a different principle, but formates are often weakly alkaline and have relatively low H reserves, low hydrogen production activity, unsatisfactory selectivity, and easily deactivate the catalyst. In view of the problems faced by formate hydrogen production, the present invention provides the following solutions:

[0010] A method for preparing a formate hydrogen production catalyst, comprising the steps of:

[0011] Step (1):

[0012] A water solution containing a Cr source, a compound of formula 1 and HF is subjected to a hydrothermal treatment, wherein the molar ratio of the Cr element, the compound of formula 1, HF and water in the water solution is 1:1-2:1-2.5:270-290; the hydrothermal temperature is 190-230° C., and the hydrothermal time is 7-13 hours;

[0013]

[0014] After hydrothermal treatment, solid-liquid separation and washing are performed to obtain a spindle-shaped Cr-based material;

[0015] Step (2):

[0016] Depositing nano-active particles on a spindle-shaped Cr-based material to obtain the formate hydrogen production catalyst, wherein the nano-active particles are Pd, Ni single substances and alloys thereof, wherein the molar ratio of Pd / Ni is 1:1.5-3;

[0017] The content in the nano active particles is greater than or equal to 1wt%.

[0018] In view of the special problems faced by formate hydrogen production, the present invention has found through in-depth research that the Cr source, the compound of formula 1 and the solution of HF are innovatively subjected to hydrothermal treatment, and the HF and other component ratios, concentrations, hydrothermal temperature, time, Pd / Ni molar ratio, content and other parameters are jointly and synergistically controlled to unexpectedly achieve synergy and obtain a special spindle-shaped Cr-based material. Moreover, Pd and Ni nanoparticles are innovatively loaded and deposited on the spindle-shaped material. In this way, based on the spindle-shaped Cr-based material and the combination of Pd and Ni, the problems of unsatisfactory reaction activity, selectivity and catalytic stability faced by the formate hydrogen production process can be synergistically solved, and the efficiency and effect of formate hydrogen production can be effectively improved.

[0019] In the present invention, the Cr source is a Cr-ion source that can ionize Cr in water. 3+ A water-soluble salt of Cr 3+ of nitrates.

[0020] In the present invention, the Cr source and Formula 1 are subjected to hydrothermal treatment in an HF solution, and the HF concentration in the starting aqueous solution and the hydrothermal temperature are jointly controlled, so that a spindle-shaped Cr-based framework material can be unexpectedly obtained. More importantly, the innovative compounding of Pd and Ni on the Cr-based material of this morphology can unexpectedly synergistically solve the problems faced by formate hydrogen production.

[0021] In the present invention, the spindle-shaped structure refers to a structure with a rod-shaped middle portion and two narrowed ends forming a polygonal cone. In the present invention, the cross section of the spindle-shaped Cr-based material is preferably hexagonal.

[0022] In the present invention, the combined control of the ratio of HF and other components in the raw material is one of the keys to unexpectedly obtain the special spindle-shaped structure, and then cooperate with the subsequent Pd / Ni to improve the activity of hydrogen production by formate hydrolysis.

[0023] Preferably, the molar ratio of Cr element, compound of formula 1, HF, and water is 1: 1-1.2: 1.4-2: 275-285; more preferably 1: 1-1.1: 1.5-2: 275-285. Under this ratio and concentration, the concentration of raw materials, especially HF, can be controlled, which is conducive to the coordinated preparation of the material with the special spindle structure, and further conducive to the coordinated improvement of the formate hydrogen production performance of the final material.

[0024] In the present invention, under the described component ratio concentration, further coordination with parameters such as hydrothermal temperature and time is conducive to obtaining the spindle structure material, and further coordination with the subsequent Pd / Ni combination can synergistically improve the performance of the prepared material in hydrogen production from formate.

[0025] In the present invention, the temperature of the hydrothermal reaction is 200-220°C.

[0026] Preferably, the hydrothermal time is 8 to 12 hours, more preferably 8 to 10 hours;

[0027] Preferably, the length of the spindle-shaped Cr-based material is 5 to 15 μm.

[0028] In the present invention, Pd and Ni are innovatively compounded on the Cr-based material of the morphology prepared in step 1, which can unexpectedly synergistically solve the problems of low activity and unstable alkali resistance faced in the hydrogen production stage of formate.

[0029] In step (2) of the present invention, Pd and Ni nanoparticles can be deposited on the spindle-shaped Cr-based material based on solution reduction; the steps are preferably: the spindle-shaped Cr-based material is dispersed in a raw material aqueous solution containing a Pd source and a Ni source, and then a reducing agent is added to carry out a reduction reaction. A further preparation method of the present invention is, for example: the spindle-shaped Cr-based material is soaked in a raw material aqueous solution containing a Pd source and a Ni source, and the soaking time can be more than one hour. Considering the processing efficiency, it can be further 6 to 30 hours. Then evaporate to dryness to obtain a precursor, and then add a solution containing a reducing agent to the precursor for reduction precipitation treatment.

[0030] In the present invention, the Pd source is Pd 2+ A water-soluble salt of Pd 2+ At least one of the nitrate, acetate, and chloride salts of

[0031] Preferably, the Ni source is Ni 2+ A water-soluble salt of Ni 2+ At least one of nitrate, acetate, chloride and sulfate;

[0032] Preferably, the reducing agent is a reducing agent capable of converting Pd 2+ 、Ni 2+ The water-soluble reducing agent that is reduced to a single substance is preferably at least one of sodium borohydride, potassium borohydride, and lithium borohydride;

[0033] Preferably, the reducing agent is not less than Pd 2+ 、Ni 2+ The theoretical molar amount for complete reduction to a simple substance is preferably 1 to 1.2 times the theoretical molar amount.

[0034] The present invention has found that, based on the spindle-shaped Cr-based material, further controlling the molar ratio of Pd / Ni can help to further improve the problems faced by formate hydrogen production. Through research, it has been found that the molar ratio of Pd / Ni is 1:1.5-2.5; it can further synergistically improve the effect of formate hydrogen production.

[0035] Preferably, the crystal size of the nano-active particles is 1 to 10 nm;

[0036] In the present invention, the total mass percentage of Pd / Ni is 1-5%, and the mass percentage of Cr in the spindle-shaped Cr-based material is 9-15%.

[0037] The present invention also provides a formate hydrogen production catalyst prepared by the preparation method.

[0038] Thanks to the preparation method, the present invention can give the prepared catalyst special physical and chemical properties and microstructures, and the material with special characteristics prepared by the preparation method can unexpectedly show excellent activity, selectivity and stability in hydrogen production from formate.

[0039] The present invention also provides a formate hydrogen production method, wherein formate is subjected to a hydrogen production reaction under the catalysis of the formate hydrogen production catalyst, and hydrogen is collected;

[0040] Preferably, the hydrogen production reaction is a liquid phase hydrogen production reaction or a solid phase hydrogen production reaction;

[0041] Preferably, the catalyst is dispersed in an aqueous solution containing formate to carry out a liquid phase hydrogen production reaction;

[0042] Preferably, the temperature in the hydrogen production reaction stage is above 10°C, preferably 20 to 80°C, and more preferably 40 to 65°C.

[0043] In the present invention, the formate can be any salt that can ionize HCOO-, for example, it can be at least one of sodium formate and potassium formate;

[0044] The present invention also provides a formate-mediated hydrogen production-storage method, wherein formate is subjected to a hydrogen production reaction under the catalysis of the formate hydrogen production catalyst of the present invention to produce hydrogen and bicarbonate materials;

[0045] Carrying out a hydrogen storage reaction between the bicarbonate material and the hydrogen to be stored to obtain formate;

[0046] According to the need of hydrogen production or storage, corresponding hydrogen production or storage reaction is carried out.

[0047] The reaction equation of the present invention under the action of the catalyst is HCOO - +H2O→H2+HCO3 - The bicarbonate produced by the reaction can also be hydrogenated (the reaction equation is H2+HCO3 - →HCOO - +H2O) to regenerate formate, thus realizing the hydrogen storage and release cycle. The catalyst of the present invention is conducive to realizing hydrogen production by hydrolysis of formate at a relatively lower temperature, and effectively solves the problems of low yield and low concentration of hydrogen produced by hydrolysis of formate in the prior art.

[0048] Beneficial effects:

[0049] 1) The present invention innovatively hydrothermally treats a solution of a Cr source, a compound of Formula 1 and HF, and unexpectedly achieves synergy through the combined synergistic control of the proportion of HF and other components, the hydrothermal temperature and other parameters, and obtains a special spindle-shaped Cr-based material. Moreover, Pd and Ni nanoparticles are innovatively loaded and deposited on the spindle-shaped material. In this way, based on the spindle-shaped Cr-based material and the combination of Pd and Ni, the problems of unsatisfactory reaction activity, selectivity and catalytic stability faced by the formate hydrogen production process can be synergistically solved, and the efficiency and effect of formate hydrogen production can be effectively improved.

[0050] Studies have shown that at 80°C, the hydrogen yield of the potassium formate hydrolysis method of the present invention can reach 80 mol·H2 / h / kg·catalyst, and the hydrogen concentration can reach 80 vol%.

[0051] 2) The catalyst described in the present invention can improve the conversion rate of formate under relatively low temperature conditions; high-purity hydrogen can be directly obtained. In addition, the bicarbonate produced by the reaction can also be regenerated into formate through a hydrogenation reaction, realizing a hydrogen storage and release cycle, which provides a new idea for solving the hydrogen storage problem. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 Schematic diagram of the scheme of the present invention;

[0053] Figure 2 The SEM, TEM and TEM scan images of the catalyst Pd1Ni2 / 200-8-1.5 of Example 1;

[0054] Figure 3 is the X-ray diffraction pattern of the catalyst and its carrier of Example 1;

[0055] Figure 4 The hydrogen production effect diagram of the catalysts of Example 1 and Example 5;

[0056] Figure 5 This is the SEM image of the catalyst carrier 200-8-1.0;

[0057] Figure 6 This is the SEM image of the catalyst carrier 200-8-2.0;

[0058] Figure 7 The SEM images of catalyst carriers 200-8-0.5 (Figure A) and 200-8-0 (Figure B);

[0059] Figure 8 This is the SEM image of the catalyst carrier 200-8-3.4;

[0060] Fig. 9 The X-ray diffraction patterns of the catalyst supports prepared under different HF addition conditions;

[0061] Fig.10 The graph of hydrogen production by catalytic formate hydrolysis in the experimental group and the comparative group in Example 2;

[0062] Fig.11 The SEM images of the catalyst supports prepared under different temperature conditions in Example 3;

[0063] Fig.12 The SEM images of the catalyst supports prepared under different hydrothermal time conditions in Example 4;

[0064] Fig.13 The SEM, TEM and TEM surface scan images of the catalyst of comparative group A of Example 5;

[0065] Fig.14 This is a graph showing the hydrogen production from formate hydrolysis catalyzed by the catalyst Pd1Ni2 / 200-8-1.5 under different temperature conditions in Example 6;

[0066] Fig.15 N2 isothermal adsorption-desorption curves of catalyst supports prepared under four typical conditions; DETAILED DESCRIPTION

[0067] The preparation of the spindle-shaped Cr-based material of the present invention is one of the keys to improve hydrogen production from formate in synergy with Pd-Ni. The spindle-shaped Cr-based material can be obtained by hydrothermal treatment of an aqueous solution containing a Cr source, a compound of formula 1 and HF in a molar ratio of 1:1-2:1-2.5:270-290 at a temperature of 190-230°C for 7-13h.

[0068] The typical steps for preparing the spindle-shaped Cr-based material of the present invention are, for example:

[0069] 1) Chromium nitrate nonahydrate and Formula 1 are dissolved in deionized water respectively, and an appropriate amount of hydrofluoric acid is added so that the molar ratio of the reactants is Cr 3+ Formula 1: HF:H2O=1:1-2:1-2.5:270-290 (preferably 1:1-1.2:1.4-2:275-285), stirring at room temperature to obtain a mixed solution of the ratio and concentration;

[0070] 2) The mixed solution obtained in step (1) is transferred to a reaction vessel and subjected to hydrothermal reaction at 200-220° C. for 8-12 hours to obtain a precipitate.

[0071] 3) washing the precipitate obtained in step (2) by centrifugation with N,N-dimethylformamide, and then repeatedly washing by centrifugation with ethanol to obtain a precipitate;

[0072] 4) placing the precipitate obtained in step (3) in an ethanol solution, soaking it at 80-90° C. for 20-24 hours, then centrifugally washing it with the ethanol solution, drying and grinding it to obtain a green powder;

[0073] 5) The powdery substance obtained in step (4) is transferred into a vacuum drying oven and vacuum dried at 150° C. for 10 to 12 hours, and a spindle-shaped Cr-based material (also labeled as MIL88Cr in the present invention) is obtained after being taken out;

[0074] In the present invention, Pd-Ni nanoparticles can be deposited on a spindle-shaped Cr-based material based on a solution precipitation method. The Pd-Ni can be independent nanoparticles, or partially or completely form an alloy. The preparation process is, for example:

[0075] a) adding a metal nitrate precursor solution dropwise to the spindle-shaped Cr-based material, and fully shaking and mixing on an oscillator to obtain a wet solid; the nitrate precursor solution is an aqueous solution containing Pd and Ni nitrates dissolved therein;

[0076] b) allowing the wet solid obtained in step (a) to stand overnight, then vacuum drying for 8 to 10 hours, and finally grinding to obtain a dry solid powder;

[0077] c) adding a NaBH4 aqueous solution dropwise to the solid powder obtained in step (b), stirring the suspension vigorously in an ice-water bath for 3 to 5 hours, centrifuging to obtain a precipitate, and then repeatedly centrifuging and washing the precipitate with deionized water;

[0078] d) transferring the precipitate obtained in step (c) into a vacuum drying oven and vacuum drying it at 80-120° C. for 10 hours to finally obtain a catalyst;

[0079] In the present invention, in step a), the metal nitrate precursor solution is a mixed solution of palladium nitrate and nickel nitrate;

[0080] In the present invention, in step a), the concentration of the metal nitrate precursor solution is 0.10 to 0.12 mol / L;

[0081] In the present invention, in step a), the metal nitrate precursor solution contains Pd 2+ and Ni 2+ The molar ratio is 1:1 to 3;

[0082] In the present invention, in step a), the amount of metal nitrate precursor solution added is 2.0-3.0 mL / g;

[0083] In the present invention, in step b), the particle size of the material after crushing and grinding is 0.1 to 0.3 mm;

[0084] In the present invention, in the step c), the concentration of the NaBH4 aqueous solution is 0.3-0.6 mol / L, and the addition amount is 8-10 mL / g;

[0085] In the present invention, in the step c), the rotation speed of the centrifugal process is 8000-10000 rpm, and the centrifugal time is 10-30 min;

[0086] In the present invention, the catalyst of the present invention can be used for formate hydrolysis to produce hydrogen based on known methods. For example, the typical application method steps of the present invention can be:

[0087] The catalyst is added to a round-bottom three-necked flask containing formate, and the three-necked flask is placed in a heat-collecting magnetic stirring water bath, and the water bath temperature is controlled at a hydrogen production temperature, such as 40-80° C., by a temperature control device. High-purity N2 is introduced into one end of the three-necked flask, and N2 and the gas produced by the reaction are discharged from the other end, and the water vapor is completely removed by a condensing device, and finally collected by an aluminum foil air bag. The collected gas is quantitatively detected for gas composition and content by gas chromatography.

[0088] In the present invention, the concentration of the formate aqueous solution is 4.0-6.0 mol / L, and the formate is, for example, potassium formate.

[0089] Example 1

[0090] 1) Mix chromium nitrate nonahydrate with formula 1, add 50 mL of deionized water to prepare a solution;

[0091] 2) adding 40% HF aqueous solution to the solution obtained in step 1), controlling the molar ratio of Cr element, compound of formula 1, HF and water in the solution system to be 1:1:1.5:280, and stirring the prepared solution at room temperature for 30 minutes;

[0092] 3) The solution obtained in step 2) is placed in a hydrothermal kettle with a 100 mL polytetrafluoroethylene liner, and then the hydrothermal kettle is placed in an oven for hydrothermal reaction at 200° C. for 8 hours. After the reaction is completed, the hydrothermal kettle is cooled to room temperature along with the oven to obtain a green suspension;

[0093] 4) The suspension obtained in step 3) was filtered through a 1° (G1) sand core funnel to remove the unreacted white solid of formula 1. 30 mL of N,N-dimethylformamide (DMF) was added to the filtrate and stirred in a water bath at 85° C. for 15 minutes to completely dissolve the excess organic acid.

[0094] 5) The solution obtained in step 4) was placed in a centrifuge tube, and centrifuged at 10,000 rpm for 10 minutes to obtain a dark green precipitate. After the supernatant was discarded, an ethanol solution was added to wash the precipitate, and the precipitate was centrifuged again. This washing step was repeated 4 times to obtain a green precipitate.

[0095] The green precipitate obtained in step 5) was transferred into a 100 mL hydrothermal autoclave, and 50 mL of ethanol was added and soaked at 80° C. for 24 hours to remove the DMF remaining in the precipitate. Finally, a pure product (also called a carrier or substrate, also named 200-8-1.5) was obtained by centrifugation, and vacuum dried at 150° C. for 12 hours to obtain a spindle-shaped Cr-based material for standby use.

[0096] 6) Accurately weigh Pd(NO3)2·2H2O solid and Ni(NO3)2·6H2O solid, dissolve them in a dilute hydrochloric acid solution with a pH of 3.0 to obtain Pd 2+ The concentration is 0.0388mol / L and Ni 2+ The precursor solution of (Pd / Ni=1:2) was stirred at room temperature for 15 minutes to obtain a clear brown-red liquid.

[0097] 7) 0.56 mL of the solution obtained in step 7) was evenly added dropwise to 500 mg of the spindle-shaped Cr-based material using a pipette to obtain a wet green solid. The solid was placed on a shaker and fully shaken, then allowed to stand overnight, and then placed in a vacuum drying oven at 150° C. for 12 hours to obtain a dry green solid;

[0098] 8) The solid powder obtained in step 8) is placed in a beaker, and 0.6 mol / L NaBH4 solution (5 mL) is quickly added dropwise. The mixture is vigorously stirred in an ice-water bath. The solution quickly turns dark green and generates a large number of bubbles. After 3 hours, the solution is transferred to a centrifuge tube and centrifuged at 8000 rpm for 10 min. The supernatant is removed and washed with deionized water. This process is repeated three times. The final dark green solid is placed in a vacuum drying oven at 80° C. and vacuum dried for 12 hours to obtain Pd1Ni2 / 200-8-1.5 catalyst (also referred to as Pd1Ni2).

[0099] The microscopic characterization results of the obtained catalyst are as follows Figure 2 , where A (A1~A3), B (B1~B3) and C (C1~C3) are transmission electron microscopy, scanning transmission electron microscopy and surface scan images under transmission electron microscopy, respectively. The surface scan results and the microscopic morphology of the catalyst show that the catalyst is a catalytic system based on a spindle-type Cr-based material with a rod-like crystal morphology with regular hexahedrons at both ends, loaded with Pd-Ni alloy nanoparticles, and the Pd-Ni alloy nanoparticles are highly uniformly dispersed on the surface of the spindle-type Cr-based material.

[0100] The X-ray diffraction characterization results of the catalyst obtained are as follows: Figure 3 , the Pd-Ni alloy doping process did not destroy the structure of the catalyst carrier, and the alloy nanoparticles in the carrier were highly dispersed, so the diffraction peak of the Pd-Ni alloy was not detected.

[0101] 9) Add 20 mg of the catalyst prepared in step 8 to a 10 mL round-bottom three-necked flask, followed by adding 5 mL of potassium formate aqueous solution with a solution concentration of 4.8 mol / L. Place the three-necked flask in a heat-collecting magnetic stirring water bath. The water bath temperature is controlled at 60°C by a temperature control device, and the magnetic rotor rotates at a constant speed of 400 rpm. High-purity N2 at a flow rate of 10 mL / min is introduced into one end of the three-necked flask, and N2 and the gas produced by the reaction are discharged from the other end. The water vapor is completely removed by a condensing device, and finally collected by an aluminum foil air bag. The collected gas is quantitatively detected for gas composition and content by gas chromatography. The results are shown in Figure 4 Pd2Ni1 curve in the figure.

[0102] Example 2—HF ratio case

[0103] Compared with Example 1, the only difference is that the ratio of the raw materials in step 2) is changed: the experimental groups are:

[0104] Group A: Compared with Example 1, the only difference is that in step 2), the molar ratio of Cr element, compound of formula 1, HF and water is 1:1:1:280. The remaining steps are the same as those in Example 1, the prepared carrier is 200-8-1, and the catalyst is named Pd1Ni2 / 200-8-1;

[0105] Group B: Compared with Example 1, the only difference is that in step 2), the molar ratio of Cr element, compound of formula 1, HF and water is 1:1:2:280. The remaining steps are the same as those in Example 1, the prepared carrier is 200-8-2, and the catalyst is named Pd1Ni2 / 200-8-2;

[0106] Comparative group A: Compared with Example 1, the only difference is that in step 2), the molar ratio of Cr element, compound of formula 1, HF and water is 1:1:0.5:280. The remaining steps are the same as those in Example 1, the prepared carrier is 200-8-0.5, and the catalyst is named Pd1Ni2 / 200-8-0.5;

[0107] Comparative group B: Compared with Example 1, the only difference is that in step 2), HF is not added, that is, the molar ratio of Cr element, compound of formula 1, HF and water is 1:1:0:280; the remaining steps are the same as in Example 1, the prepared carrier is 200-8-0, and the catalyst is named Pd1Ni2 / 200-8-0;

[0108] Comparative group C: Compared with Example 1, the only difference is that in step 2), the molar ratio of Cr element, compound of formula 1, HF and water is 1:1:3.4:280, and the remaining steps are the same as Example 1; the carrier is labeled 200-8-3.4;

[0109] Figure 5 This is a SEM image of the catalyst carrier Pd1Ni2 / 200-8-1 of the experimental group A. The carrier is a mixture of regular octahedron and spindle rod, wherein the regular octahedron particle size is about 1.0 μm, and the spindle rod particle length is 5-10 μm;

[0110] Figure 6 This is a SEM image of the catalyst carrier Pd1Ni2 / 200-8-2 of the experimental group B. The carrier is a spindle rod structure with a length of 5-10 μm;

[0111] Figure 7 A is a SEM image of the catalyst carrier 200-8-0.5 described in comparison group A. The carrier is a regular octahedron with a particle size of 0.5-1.0 μm, which is slightly larger than the carrier described in comparison group A; Figure 7 B is the SEM image of the catalyst carrier 200-8-0 in the comparative group B. The carrier is a regular octahedron with a particle size of 0.3-0.8 μm

[0112] Figure 8 The SEM image of the catalyst carrier 200-8-3.4 described in comparison group C shows that the synthesized product is partially stacked layered structure and partially particles with irregular surface. The particle size distribution is 1-10 μm. There are also a small amount of incomplete spindle-rod structures. The spindle-rod-shaped carrier described in Example 1 was not successfully prepared at this HF concentration, and the regular octahedral carrier described in comparison group A in Example 2 was not prepared. Therefore, 200-8-3.4 was not used as a catalyst carrier.

[0113] Fig. 9 The X-ray diffraction results of the catalyst carriers described in the above embodiments and comparative examples show that no obvious diffraction peaks of the active components are found. It can be seen that the active components are evenly dispersed in each embodiment, and the diffraction peaks mainly come from the substrates of the catalysts of the above embodiments and comparative examples. On the other hand, it can be found that carrier 200-8-1.5 has strong peaks at 2θ of 10.34° and 20.78°, carrier 200-8-0 and carrier 200-8-0.5 have strong peaks at 2θ of 5.09°, 5.62°, 5.86°, 8.42°, and 9.06°, while carrier 200-8-1.0 has both peaks at 2θ of 10.34° and 20.78°, and peaks at 2θ of 5.09°, 5.62°, 5.86°, 8.42°, and 9.06°. .06° peak, it can be seen that the spindle rod-shaped carrier 200-8-1.5 (also marked as MIL88Cr) and the octahedral carriers 200-8-0 and 200-8-0.5 belong to different materials in crystal structure, while the octahedral carriers 200-8-0 and 200-8-0.5 belong to the same material in crystal structure (also marked as MIL101Cr), and the carrier 200-8-1.0 is a mixture of the above two materials.

[0114] The formate hydrogen production rate and product hydrogen purity were measured according to the method of Example 1. The results are shown in Fig.10 .

[0115] Example 3 - Hydrothermal Temperature Case

[0116] Compared with Example 1, the only difference is that the hydrothermal temperature in step 3) is changed, and the experimental groups are:

[0117] A: Compared with Example 1, the only difference is that the hydrothermal temperature is 210°C, and the other operations and parameters are the same as Example 1. The obtained catalyst carrier is named 210-8-1.5;

[0118] B: Compared with Example 1, the only difference is that the hydrothermal temperature is 220°C. The remaining steps are the same as those in Example 1, and the obtained catalyst carrier is named 220-8-1.5;

[0119] Comparative group A: Compared with Example 1, the only difference is that the hydrothermal temperature is 180°C. The remaining steps are the same as Example 1, and the obtained catalyst carrier is named 180-8-1.5;

[0120] Comparative group B: Compared with Example 1, the only difference is that the hydrothermal temperature is 240°C. The remaining steps are the same as Example 1, and the obtained catalyst carrier is named 240-8-1.5;

[0121] Fig.11 A is a SEM image of the catalyst carrier 210-8-1.5 in the experimental group A. The carrier is a spindle rod structure with a length of 5-10 μm and has similar morphological characteristics to the carrier described in Example 1;

[0122] Fig.11 B is a SEM image of the catalyst carrier 220-8-1.5 described in Experimental Group B. The carrier is a spindle rod-like structure with a length of 5-10 μm, and has similar morphological characteristics to the carrier described in Example 1;

[0123] Fig.11 C is a SEM image of the catalyst carrier 180-8-1.5 described in the comparative group A. The carrier is a mixture of regular octahedrons and rods, and most of them are block structures with irregular surfaces. This phenomenon shows that under this condition, the spindle rod-shaped carrier described in Example 1 was not successfully prepared, and the regular octahedron carrier described in the comparative group A in Example 2 was not successfully prepared;

[0124] Fig.11 D is the SEM image of the catalyst carrier 240-8-1.5 described in comparison group B. Most of the carriers are block structures with irregular surfaces and particle sizes exceeding 5 μm. The spindle rod-shaped carrier described in Example 1 was not successfully prepared, and the regular octahedral carrier described in comparison group A in Example 2 was also not prepared.

[0125] Example 4 - Hydrothermal Time Case

[0126] Compared with Example 1, the only difference is that the hydrothermal time of step 3 is changed, and the experimental groups are:

[0127] A: Compared with Example 1, the only difference is that the hydrothermal time of step 3 is 10 hours. The remaining steps are the same as Example 1, and the obtained catalyst carrier is named 200-10-1.5;

[0128] B: Compared with Example 1, the only difference is that the hydrothermal time of step 3 is 12 hours. The remaining steps are the same as those of Example 1, and the obtained catalyst carrier is named 200-12-1.5;

[0129] Comparative group A: Compared with Example 1, the only difference is that the hydrothermal time of step 3 is 6 hours. The remaining steps are the same as Example 1, and the obtained catalyst carrier is named 200-6-1.5;

[0130] Comparative Group B: Compared with Example 1, the only difference is that the hydrothermal time of step 3 is 18 hours. The remaining steps are the same as Example 1, and the obtained catalyst carrier is named 200-18-1.5;

[0131] Fig.12 A is a SEM image of the catalyst carrier 200-10-1.5 in experimental group A, the carrier is a slender spindle rod structure with a length of 5-15 μm;

[0132] Fig.12 B is a SEM image of the catalyst carrier 200-12-1.5 in the experimental group B, the carrier is a slender spindle rod structure with a length of 5-15 μm;

[0133] Fig.12 C is a SEM image of the catalyst carrier 200-6-1.5 described in comparison group A, which is a mixture of regular octahedron and rod-shaped carriers, wherein the regular octahedron particle size is less than 1.0 μm, the rod-shaped particle length is less than 5 μm, and there are irregularly shaped particles with a particle size less than 1.0 μm. The spindle rod-shaped carrier described in Example 1 cannot be fully synthesized, and the regular octahedron carrier described in comparison group A in Example 2 cannot be prepared;

[0134] Fig.12 D is the SEM image of the catalyst carrier 200-18-1.5 in comparison group B. The carrier is a stacked layered structure with a particle size distribution of 1-10 μm. There is also a small amount of spindle-rod-shaped carrier. The main component of the carrier synthesized under this condition is no longer the spindle-rod-shaped carrier described in Example 1.

[0135] 2. Examples of Pd / Ni ratio and loading amount:

[0136] Example 5

[0137] Compared with Example 1, the only difference is that the molar ratio of Pd / Ni in step 6 is changed, and the total molar amount of Pd / Ni in step 7 remains unchanged. The experimental groups are:

[0138] A: Compared with Example 1, the only difference is that the molar ratio of Pd / Ni in step 6 is 1:1, and the other operations and parameters are the same as Example 1; the final product prepared is marked as Pd1Ni1 / 200-8-1.5.

[0139] B: Compared with Example 1, the only difference is that the molar ratio of Pd / Ni in step 6 is 2:1, and the other operations and parameters are the same as those in Example 1; the final product prepared is marked as Pd2Ni1 / 200-8-1.5.

[0140] Comparative Example A: Compared with Example 1, the only difference is that step 6 does not contain Ni 2+ The missing part is supplemented by an equimolar amount of Pd. Other operations and parameters are the same as those in Example 1; the final product is labeled as Pd / 200-8-1.5;

[0141] The microscopic characterization results of the catalyst obtained in Comparative Example A are as follows Fig.13 .

[0142] According to the method of Example 1, the formate hydrogen production rate and the product hydrogen purity of each experimental group and the comparison group were measured. The results are shown in Figure 4 . Figure 4 In the figure, Pd2Ni1 represents the Example 5B group; Pd1Ni1 represents the Example 5A group, and Pd represents the Comparative Example A group.

[0143] 3. Screening cases of application conditions

[0144] 3.1: Example of hydrogen production temperature

[0145] Example 6

[0146] Compared with Example 1, the only difference is that the temperature of the hydrogen production stage in step 9) is changed. The experimental groups are:

[0147] A: Compared with Example 1, the only difference is that the formate hydrolysis reaction temperature is 40-80°C. The formate hydrolysis hydrogen production rate and the product hydrogen purity are measured. The results are shown in Fig.14 .

[0148] After determining the best catalyst, the reaction temperature was optimized, with hydrogen yield and hydrogen concentration as indicators. The results are as follows: Fig.14 As shown in the results of hydrogen yield and hydrogen concentration in the temperature range of 40-80℃, it can be found that as the temperature increases, the hydrogen yield gradually increases, and at the same time, the concentration of CO2 produced increases accordingly. 60℃ is the optimal temperature for catalytic hydrolysis of potassium formate. At this temperature, the hydrogen yield is high, and the CO2 produced is relatively small, and the hydrogen concentration can be as high as 84% ​​or more.

[0149] Fig.15The N2 adsorption-desorption curves of the four typical catalyst carriers described in the above examples and comparative examples are shown in Table 1. The specific surface area and pore volume of each example are calculated using the BET formula. It can be found that the N2 adsorption-desorption curves of carrier 200-8-0 and carrier 200-8-0.5 are typical type I (b) adsorption isotherms, and there is a steep step shape at the position where p / p0 is about 0.2, indicating that there are two different types of mesopores in the carrier with a regular octahedral structure. The carrier 200-8-1.5 synthesized in Example 1 is mainly a spindle rod structure, and almost does not contain a regular octahedral structure. The specific surface area calculated using the BET formula is much lower than that of the regular octahedral structure carrier, and the porosity is relatively low. Carrier 200-8-1.0 is a mixture of regular octahedral structure and spindle rod structure, so the specific surface area and pore volume are between carrier 200-8-0 and carrier 200-8-1.5.

[0150] Table 1 Comparison of carrier structure parameters and performance in Examples and Comparative Examples

[0151]

Claims

1. A method for preparing a formate hydrogen production catalyst, characterized in that the steps include: Step (1): A water solution containing a Cr source, a compound of formula 1 and HF is subjected to a hydrothermal treatment, wherein the molar ratio of the Cr element, the compound of formula 1, HF and water in the water solution is 1:1-2:1-2.5:270-290; the hydrothermal temperature is 190-230° C., and the hydrothermal time is 7-13 hours; After hydrothermal treatment, solid-liquid separation and washing are performed to obtain a spindle-shaped Cr-based material; Step (2): Depositing nano-active particles on a spindle-shaped Cr-based material to obtain the formate hydrogen production catalyst, wherein the nano-active particles are Pd, Ni single substances and alloys thereof, wherein the molar ratio of Pd / Ni is 1:1.5-3; The content in the nano active particles is greater than or equal to 1wt%.

2. The method for preparing a formate hydrogen production catalyst according to claim 1, wherein: The Cr source is a Cr source that can ionize Cr in water. 3+ A water-soluble salt of Cr 3+ of nitrates; Preferably, in the aqueous solution, the molar ratio of Cr element, the compound of formula 1, HF and water is 1:1-1.2:1.4-2:275-285.

3. The method for preparing a formate hydrogen production catalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 200-220°C; Preferably, the hydrothermal time is 8 to 12 hours, more preferably 8 to 10 hours; Preferably, the length of the spindle-shaped Cr-based material is 5 to 15 μm.

4. The method for preparing a formate hydrogen production catalyst according to claim 1, characterized in that: In step (2), Pd and Ni nanoparticles are deposited on the spindle-shaped Cr-based material by solution reduction; The steps are preferably as follows: dispersing the spindle-shaped Cr-based material in a raw material aqueous solution containing a Pd source and a Ni source, then adding a reducing agent to carry out a reduction reaction, thereby obtaining the obtained material.

5. The method for preparing a formate hydrogen production catalyst according to claim 4, characterized in that: The Pd source is Pd 2+ A water-soluble salt of Pd 2+ At least one of the nitrate, acetate, and chloride salts of Preferably, the Ni source is Ni 2+ A water-soluble salt of Ni 2+ At least one of nitrate, acetate, chloride and sulfate; Preferably, the reducing agent is a reducing agent capable of converting Pd 2+ 、Ni 2+ The water-soluble reducing agent that is reduced to a single substance is preferably at least one of sodium borohydride, potassium borohydride, and lithium borohydride; Preferably, the reducing agent is not less than Pd 2+ 、Ni 2+ The theoretical molar amount for complete reduction to a simple substance is preferably 1 to 1.2 times the theoretical molar amount.

6. The method for preparing a formate hydrogen production catalyst according to claim 1, 4 or 5, characterized in that: The molar ratio of Pd / Ni is 1:1.5-2.

5.

7. The method for preparing a formate hydrogen production catalyst according to claim 6, wherein: The grain size of nano-active particles is 1 to 10 nm; Preferably, the total mass percentage of Pd / Ni is 1-5%, and the mass percentage of Cr in the spindle-shaped Cr-based material is 9-15%.

8. A formate hydrogen production catalyst prepared by the preparation method according to any one of claims 1 to 7.

9. A method for producing hydrogen from formate, characterized in that: Carrying out a hydrogen production reaction on the formate under the catalysis of the formate hydrogen production catalyst prepared by the preparation method according to any one of claims 1 to 7, and collecting the obtained hydrogen; Preferably, the hydrogen production reaction is a liquid phase hydrogen production reaction or a solid phase hydrogen production reaction; Preferably, the catalyst is dispersed in an aqueous solution containing formate to carry out a liquid phase hydrogen production reaction; Preferably, the temperature in the hydrogen production reaction stage is above 10°C, preferably 20 to 80°C, and more preferably 40 to 65°C; Preferably, the formate is at least one of sodium formate and potassium formate.

10. A formate-mediated hydrogen production and storage method, characterized in that: The formate is subjected to a hydrogen production reaction by the method of claim 9 to produce hydrogen and bicarbonate materials; Carrying out a hydrogen storage reaction between the bicarbonate material and the hydrogen to be stored to obtain formate; According to the need of hydrogen production or storage, corresponding hydrogen production or storage reaction is carried out.